Utilizing Google Classroom to Encourage Changes in Students' Learning Culture and Academic Discipline: A Case Study of Online Learning - Ahmad Sultoni Matondang; Afnan Siregar; Muhammad Gani Ray; Sholeh Fikri (Konsultan Jurnal Ilmiah Indonesia, 2026)
The use of online learning platforms is increasingly playing an important role in shaping student learning patterns, culture, and discipline. This study aims to analyze the role of Google Classroom in encouraging changes in students' learning culture and academic discipline in the context of online learning. The research uses a qualitative approach with a case study design carried out in educational units in small-scale urban areas. Data was collected through an online questionnaire that was distributed to students to explore their perceptions, experiences, and learning habits while using Google Classroom. Data analysis was carried out in a descriptive-thematic manner by grouping findings based on indicators of technology acceptance, learning independence, academic discipline, and learning culture. The analytical framework of this research refers to Social Constructivism, Technology Acceptance Model, Theory of Planned Behavior, and Self-Directed Learning. The results show that the perception of the convenience and usefulness of Google Classroom encourages student learning independence, which has implications for improving academic discipline and the formation of a more structured and responsible online learning culture. This research makes a practical contribution to the development of adaptive and contextual online learning.